Kinetic parameters of red pepper waste as biomass to solid biofuel - Maia, Amanda Alves Domingos [UNESP]; de Morais, Leandro Cardoso [UNESP] (Elsevier, 2016)
This work aimed to study the kinetic of thermal degradation of red pepper waste as solid biofuel to bioenergy production. The thermal degradation experiments were conducted at three heating rates, 5 °C/min, 7.5 °C/min and 10 °C/min in a thermogravimetric analyzer and oxidative atmosphere. The kinetic analysis was carried out applying the isoconversional model of Ozawa-Flynn-Wall. The activation energy was considerate low and varied 29.49-147.25 kJ/mol. The enthalpies revealed the energy difference between the reagent and the activated complex agreed with activation energies, the values of the pre-exponential factor indicated empirical first order reactions, Gibbs free energy varied from 71.77 kJ/mol to 207.03 kJ/mol and the changes of entropies had negative values, indicating that the degree of disorder of products formed through bond dissociations was lower than initial reactants. The calorific value was 19.5 MJ/kg, considered a relevant result for bioenergy production.
Keywords: Bioenergy; Biomass; Calorific value; Kinetics parameters; Thermal analysis